Fourier analysis and imaging - Bracewell, Ronald N. (Ronald Newbold), 1921-2007. (New York : Kluwer Academic Publishers, 2004)
"Fourier Analysis and Imaging is based on years of teaching a course on the Fourier transform at the senior or early graduate level, as well as on Prof. Bracewell's 1995 text Two-Dimensional Imaging. It is an excellent textbook and will also be a welcome addition to the reference library of those many professionals whose daily activities involve Fourier analysis in its many guises."--BOOK JACKET.
1. Introduction -- 2. The Image Plane -- 3. Two-Dimensional Impulse Functions -- 4. The Two-Dimensional Fourier Transform -- 5. Two-Dimensional Convolution -- 6. The Two-Dimensional Convolution Theorem -- 7. Sampling and Interpolation in Two Dimensions -- 8. Digital Operations -- 9. Rotational Symmetry -- 10. Imaging by Convolution -- 11. Diffraction Theory of Sensors and Radiators -- 12. Aperture Synthesis and Interferometry -- 13. Restoration -- 14. The Projection-Slice Theorem -- 15. Computed Tomography -- 16. Synthetic-Aperture Radar -- 17. Two-Dimensional Noise Images -- App. A. Solutions to Problems.
Includes bibliographical references and index.
Keywords: Imaging systems in medicine -- Mathematics; Fourier analysis; Image processing -- Digital techniques -- Mathematics; Fourier Analysis; Tomography, X-Ray Computed -- instrumentation